A bioinspired broadband self-powered photodetector based on photo-pyroelectric-thermoelectric effect able to detect human radiation. (March 2022) - Liu, Sixiang; Tian, Junlong; Wu, Shu; Zhang, Wang; Luo, Minyuan
Abstract: The self-powered broadband photodetectors based on pyro-phototronic effect or photothermoelectric effect are promising for diverse applications. Here, we propose a polar bear-inspired self-powered and uncooled broadband photodetector based on the coupled effect of pyro-photoronic and photothermoelectric effect, which integrates wurtzite structured CdS pyroelectric-thermoelectric materials with energy-harvest and heat-storing functional structures, besides cooperates with asymmetric Schottky junction by constructing an asymmetric pair of Ag electrodes. The peak-to-peak current, specific responsivity and detectivity are all enhanced by 11 times, attributed to the synergy between photopyroelectric effect and photothermoelectric effect. Significantly, for a low-power long-wave infrared radiation, it still achieves outstanding response on human radiation, when the separation between human finger and detector is extended to 10 cm. This study provides a novel design to achieve the synergy of photopyroelectric effect and photothermoelectric effect, and opens up a new avenue towards upgrading the performance of optoelectronic devices and energy harvesters for extensive applications. Graphical Abstract: ga1 Highlights: This work achieves the synergy of photopyroelectric effect and photothermoelectric effect to enhance the broadband sensing, innovatively. It effectively overcomes the limits of the PDs which base on photopyroelectric effect and photothermoelectric effect solos. It shows an excellent performance on human radiation detecting.